Interventions Promoting Physical Activity in African American Women: An Integrative Review - Jenkins, Felicia (J Cardiovasc Nurs, 2017)
BACKGROUND: Physical inactivity significantly impacts mortality worldwide. Physical inactivity is a modifiable risk factor for obesity, diabetes, cardiovascular disease, and other chronic conditions. African American women in the U.S. have the highest rates of physical inactivity when compared to other gender/ethnic groups.(1) A paucity of research promoting physical activity (PA) in African American women has been previously identified. The purpose of this review was to identify intervention strategies and outcomes in studies designed to promote PA in African American women. METHODS: Interventions that promoted PA in African American women published between 2000 and May 2015 were included. A comprehensive search of the literature was performed in Health Source: Nursing/Academic Edition, PsycINFO, CINAHL Complete, and MEDLINE Complete databases. Data were abstracted and synthesized to examine interventions, study designs, theoretical frameworks, and measures of PA. RESULTS: Mixed findings (both significant and nonsignificant) were identified. Interventions included faith-based, group-based, and individually focused programs. All studies (n = 32) included measures of PA; among the studies, self-report was the predominant method for obtaining information. Half of the 32 studies focused on PA, and the remaining studies focused on PA and nutrition. Most studies reported an increase in PA or adherence to PA. This review reveals promising strategies for promoting PA. CONCLUSIONS: Future studies should include long-term follow-up, larger sample sizes, and objective measures of PA. Additional research promoting PA in African American women is warranted, particularly in studies that focus on increasing PA in older African American women.